Tiller population density in deferred Urochroa decumbens pasture and strategies for nitrogen fertilization - doi: 10.4025/actascianimsci.v35i1.10243 - Fábio Andrade Teixeira; Paulo Bonomo; Aureliano José Vieira Pires; Fabiano Ferreira Silva; George Abreu Filho; Pablo Teixeira Viana (Acta Scientiarum. Animal Sciences, 2012)
The objective of this work was to evaluate the tiller population density in Urochroa decumbens pasture deferred for 95 and 140 days, aiming to determine the best strategy for nitrogen fertilization. Four fertilization strategies at the beginning and end of summer (0-0, 100-0, 50-50, 0-100 kg ha-1 of N) were studied, respectively, with four repetitions. For the pastures deferred for 95 days, the population densities of vegetative tillers were greater (p < 0.05) for the strategy 0-100. At the end of the deferment period, the weight of the vegetative tillers per hectare was greater for the strategy 0-100, followed by the strategy 50-50. The densities of vegetative tillers, evaluated in the pastures deferred for 140 days, were greater (p < 0.05) for the fertilization strategies 0-100 and divided 50-50. At the end of the deferment period, greater density (p < 0.05) of dead tillers was verified for the fertilization strategy 0-100, not proving effect (p < 0.05) in post-grazing. The strategy of application of 100 kg ha-1 at the end of summer, followed by the strategy of 50 kg ha-1 of nitrogen divided between the beginning and end of summer, promoted a positive influence on the tiller population density in pastures deferred for 140 days.